Stabilization with Decay Estimate for Inhomogeneous Semilinear Control Systems using Unbounded Controls - Chqondi, M.; Baddi, M.; Akdim, Y. (Journal of Applied Nonlinear Dynamics, 2026)
This research paper examines the problem of stabilizing inhomogeneous semilinear control systems in Hilbert state space. The paper proposes a feedback control that can achieve both strong and weak stabilization under certain assumptions related to approximate observability. The provided applications of the proposed method include the nonlinear Schroedinger equation and heat equation.